Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To prove that [tex]\(\sum_{i=1}^n \left(x_i - \mu\right)^2 = \sum_{i=1}^n x_i^2 - n \mu^2\)[/tex], we will start by expanding the left side and then simplifying it to match the right side.
### Step 1: Define the mean
The mean, [tex]\(\mu\)[/tex], of the [tex]\(n\)[/tex] elements [tex]\(x_1, x_2, \ldots, x_n\)[/tex] is:
[tex]\[ \mu = \frac{1}{n} \sum_{i=1}^n x_i \][/tex]
### Step 2: Expand the left side
Let's start by expanding the left-hand side of the equation:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 \][/tex]
Expanding this, we get:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n (x_i^2 - 2x_i \mu + \mu^2) \][/tex]
### Step 3: Distribute the summation
We can distribute the summation over the terms in the expanded expression:
[tex]\[ \sum_{i=1}^n x_i^2 - \sum_{i=1}^n 2x_i \mu + \sum_{i=1}^n \mu^2 \][/tex]
### Step 4: Simplify each term
Let's simplify each term step-by-step:
1. First term:
[tex]\[ \sum_{i=1}^n x_i^2 \][/tex]
This term remains as is.
2. Second term:
[tex]\[ \sum_{i=1}^n 2x_i \mu = 2\mu \sum_{i=1}^n x_i \][/tex]
Since [tex]\(\mu\)[/tex] is a constant with respect to the summation, it can be taken outside the summation sign.
3. Third term:
[tex]\[ \sum_{i=1}^n \mu^2 \][/tex]
Since [tex]\(\mu^2\)[/tex] is also a constant with respect to the summation:
[tex]\[ \sum_{i=1}^n \mu^2 = n \mu^2 \][/tex]
### Step 5: Combine the simplified terms
Now, combining the simplified terms, we have:
[tex]\[ \sum_{i=1}^n x_i^2 - 2\mu \sum_{i=1}^n x_i + n \mu^2 \][/tex]
### Step 6: Substitute the expression for the mean
Recall that [tex]\(\mu = \frac{1}{n} \sum_{i=1}^n x_i\)[/tex]. Therefore:
[tex]\[ 2\mu \sum_{i=1}^n x_i = 2 \left(\frac{1}{n} \sum_{i=1}^n x_i\right) \sum_{i=1}^n x_i = 2 \frac{1}{n} \left(\sum_{i=1}^n x_i\right)^2 = \frac{2}{n} \left(\sum_{i=1}^n x_i\right) \sum_{i=1}^n x_i = 2 \sum_{i=1}^n x_i \][/tex]
### Step 7: Final expression
Putting it all together:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n x_i^2 - 2\mu \sum_{i=1}^n x_i + n \mu^2 = \sum_{i=1}^n x_i^2 - 2 \sum_{i=1}^n x_i \mu + n \mu^2 \][/tex]
Finally, notice that [tex]\(\sum_{i=1}^n x_i \mu = \sum_{i=1}^n \mu x_i = n \mu \mu = n\mu^2\)[/tex] as [tex]\(\mu = \frac{1}{n} \sum_{i=1}^n x_i\)[/tex]:
[tex]\[ = \sum_{i=1}^n x_i^2 - 2n \mu^2 + n \mu^2 = \sum_{i=1}^n x_i^2 - n \mu^2 \][/tex]
Hence, we have:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n x_i^2 - n \mu^2 \][/tex]
This completes the proof.
### Step 1: Define the mean
The mean, [tex]\(\mu\)[/tex], of the [tex]\(n\)[/tex] elements [tex]\(x_1, x_2, \ldots, x_n\)[/tex] is:
[tex]\[ \mu = \frac{1}{n} \sum_{i=1}^n x_i \][/tex]
### Step 2: Expand the left side
Let's start by expanding the left-hand side of the equation:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 \][/tex]
Expanding this, we get:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n (x_i^2 - 2x_i \mu + \mu^2) \][/tex]
### Step 3: Distribute the summation
We can distribute the summation over the terms in the expanded expression:
[tex]\[ \sum_{i=1}^n x_i^2 - \sum_{i=1}^n 2x_i \mu + \sum_{i=1}^n \mu^2 \][/tex]
### Step 4: Simplify each term
Let's simplify each term step-by-step:
1. First term:
[tex]\[ \sum_{i=1}^n x_i^2 \][/tex]
This term remains as is.
2. Second term:
[tex]\[ \sum_{i=1}^n 2x_i \mu = 2\mu \sum_{i=1}^n x_i \][/tex]
Since [tex]\(\mu\)[/tex] is a constant with respect to the summation, it can be taken outside the summation sign.
3. Third term:
[tex]\[ \sum_{i=1}^n \mu^2 \][/tex]
Since [tex]\(\mu^2\)[/tex] is also a constant with respect to the summation:
[tex]\[ \sum_{i=1}^n \mu^2 = n \mu^2 \][/tex]
### Step 5: Combine the simplified terms
Now, combining the simplified terms, we have:
[tex]\[ \sum_{i=1}^n x_i^2 - 2\mu \sum_{i=1}^n x_i + n \mu^2 \][/tex]
### Step 6: Substitute the expression for the mean
Recall that [tex]\(\mu = \frac{1}{n} \sum_{i=1}^n x_i\)[/tex]. Therefore:
[tex]\[ 2\mu \sum_{i=1}^n x_i = 2 \left(\frac{1}{n} \sum_{i=1}^n x_i\right) \sum_{i=1}^n x_i = 2 \frac{1}{n} \left(\sum_{i=1}^n x_i\right)^2 = \frac{2}{n} \left(\sum_{i=1}^n x_i\right) \sum_{i=1}^n x_i = 2 \sum_{i=1}^n x_i \][/tex]
### Step 7: Final expression
Putting it all together:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n x_i^2 - 2\mu \sum_{i=1}^n x_i + n \mu^2 = \sum_{i=1}^n x_i^2 - 2 \sum_{i=1}^n x_i \mu + n \mu^2 \][/tex]
Finally, notice that [tex]\(\sum_{i=1}^n x_i \mu = \sum_{i=1}^n \mu x_i = n \mu \mu = n\mu^2\)[/tex] as [tex]\(\mu = \frac{1}{n} \sum_{i=1}^n x_i\)[/tex]:
[tex]\[ = \sum_{i=1}^n x_i^2 - 2n \mu^2 + n \mu^2 = \sum_{i=1}^n x_i^2 - n \mu^2 \][/tex]
Hence, we have:
[tex]\[ \sum_{i=1}^n (x_i - \mu)^2 = \sum_{i=1}^n x_i^2 - n \mu^2 \][/tex]
This completes the proof.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.